Mentalizing the modern world. Issue 3 (3rd July 2022) - Campbell, Chloe; Allison, Elizabeth
Abstract : A theoretical paper in which the theory of mentalizing and epistemic trust are applied to thinking about the relationship between social systems and individual subjective experiences, and how this relationship may be shaped by developmental history, such as attachment experiences, exposure to childhood adversity, and the experience of being mentalized. We suggest that the experience of being mentalized and openness to epistemic trust may be the mechanism by which individual experiences of psychic distress, perception of self-agency and perceptions of others, are both influenced by and shape wider social phenomena and social change. We consider the impact of social inequalities and the breakdown of political legitimacy on mentalizing, epistemic trust and psychopathology, and argue that optimal individual outcomes cannot always be achieved without adaptation of the wider social environment.